2006
DOI: 10.1128/aem.72.2.1027-1033.2006
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Fecal Microbiota in Different European Study Populations in Relation to Age, Gender, and Country: a Cross-Sectional Study

Abstract: A cross-sectional study on intestinal microbiota composition was performed on 230 healthy subjects at four European locations in France, Germany, Italy, and Sweden. The study participants were assigned to two age groups: 20 to 50 years (mean age, 35 years; n ‫؍‬ 85) and >60 years (mean age, 75 years; n ‫؍‬ 145). A set of 14 group-and species-specific 16S rRNA-targeted oligonucleotide probes was applied to the analysis of fecal samples by fluorescence in situ hybridization coupled with flow cytometry. Marked co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

60
632
9
8

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 876 publications
(709 citation statements)
references
References 49 publications
60
632
9
8
Order By: Relevance
“…Secondly, the detection limit of FISH is approximately 0.1% (equal to 1 target cell if 1000 DAPI-stained cells are counted). Harmsen et al (1999Harmsen et al ( , 2002 and Mueller et al (2006) detected between 0.01 and 0.2% of total DAPI counts in faeces using the group-specific probe LAB158. In consideration of the species specificity of the Lba probe used in this study (Pot et al, 1993) relatively high values were observed.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, the detection limit of FISH is approximately 0.1% (equal to 1 target cell if 1000 DAPI-stained cells are counted). Harmsen et al (1999Harmsen et al ( , 2002 and Mueller et al (2006) detected between 0.01 and 0.2% of total DAPI counts in faeces using the group-specific probe LAB158. In consideration of the species specificity of the Lba probe used in this study (Pot et al, 1993) relatively high values were observed.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, increasing evidence suggests that aging is associated with alterations in the gut microbiota (Bartosch et al 2004;Biagi et al 2010;Gavini et al 2001;Hopkins et al 2001;Hopkins and Macfarlane 2002;Mueller et al 2006;Woodmansey et al 2004). Moreover, elderly subjects living in hospitals and nursing homes are susceptible to increased pathogen challenges.…”
Section: Introductionmentioning
confidence: 99%
“…A reduction in total gene counts in faecal samples from 178 elderly subjects in long-term care compared with those in the community illustrates the reduction in gut microbiota biodiversity, which is associated with frailty, morbidity and poor nutritional status in elderly subjects (1) . Also commonly reported is an age-related increase in facultative anaerobes, including streptococci, staphylococci, enterococci and enterobacteria (4)(5)(6)(7) . These are sometimes referred to as 'pathobionts'; bacteria, which are present at low concentrations in the healthy gut microbiota, but thrive in inflamed conditions and actively promote the inflammation by producing inflammatory stimuli (7) .…”
Section: Influence Of Ageing On the Gut Microbiota Compositionmentioning
confidence: 99%